DAMPAK JANGKA PANJANG PERTUMBUHAN PENDUDUK TERHADAP INVESTASI AGREGAT PROVINSI DI INDONESIA - Paulina, Paulina (Economic Faculty, Attahiriyah Islamic University, 2019)
This study aims to determine the causality relationship between population growth of a country / region (PG) which has an impact on the formation of investment (TINV) and economic growth (EG). This research was focused on 33 provinces in Indonesia on these 3 main variables. The data used are secondary data from 33 provinces, with observations between 2015-2017. The analysis models used are unit root and cointegration tests, VAR estimation and long-term VECM models, and panel data. The results of this study indicate: (1) there is no causal relationship between PG, TINV, and EG; (2) The cointegration test and the VAR model shows that there is a long-term relationship between endogenous and exogenous variables; (3) In the VECM model, there appears to be an influence between PG, EG on investment in the long run; (4) there are quite good investment provinces namely DKI Jakarta, and most of the eastern provinces of Indonesia experience positive investment rates. Keywords: population growth, formation of investmen, economic growth